Malignant Epidermoid Cyst: MRI Evaluation and Review of Literature - Jha, Nivedita; Kumar, Amit (Nepal Journal of Neuroscience, 2022)
Epidermoid cysts are commonly encountered intracranial neoplastic masses in clinical radiology practice. They are purely benign but may undergo malignant transformation or may present as de novo malignant epidermoid tumor, a rare but ominous phenomenon associated with poor prognosis. Malignant epidermoids may masquerade as glial tumours, ependymal neoplasms, or choroid plexus masses, and are prone to be misdiagnosed. We describe a case of malignant epidermoid cyst or tumor (de novo) in a young adult who presented with the complaints of intermittent headaches which had increased in frequency and severity.